Arthritis increases the risk of erectile dysfunction: Results from the NHANES 2001-2004 - Liu, Changjin; Lei, Qiming; Li, Jianwei; Liu, Weihui (Frontiers in Endocrinology, 2024)
Objective This study assessed the association between erectile dysfunction (ED) and arthritis. Methods Weighted logistic regression and subgroup analyses were used to investigate the association between arthritis incidence and ED among participants in the 2001–2004 National Health and Nutrition Examination Survey database. Results Among the participants, 27.8% and 18.5% had a self-reported history of ED and arthritis, respectively. ED was associated with arthritis (odds ratio [OR]=4.00; 95% confidence interval [CI]: 3.20–4.99; p<0.001], which remained significant after adjustment (OR=1.42, 95% CI: 1.00–1.96; p<0.001). Stratified by type of arthritis, after full adjustment, osteoarthritis remained significant (OR=1.11; 95% CI: 1.03–1.20; p=0.017), and rheumatoid arthritis (OR=1.03, 95% CI: 0.93–1.13; p= 0.5) and other arthritis (OR=1.04, 95% CI: 0.98–1.11; p=0.2) were not significantly correlated with ED. Multiple inference analyses confirmed the robustness of the results. Conclusion Our study showed that arthritis was strongly associated with ED. There is an urgent need to raise awareness and conduct additional research on the reasons behind this association in order to implement more scientific and rational treatment programs for patients with ED and arthritis.